Pediatric Adrenocortical Oncocytoma presenting as Cushing’s Syndrome and Peripheral Precocious Puberty: A Case Report and Review of Literature - Narayanan, Niya; Kamalanathan, Sadishkumar; Sahoo, Jayaprakash; Naik, Dukhabandhu; Kumaravel , Sambandan; Nachiappa Ganesh, Rajesh (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Oncocytic adrenocortical tumours (OATs) or oncocytomas are extremely rare and are usually benign and nonfunctional. We report the case of a 4-year old male with a right-sided, functional oncocytic adrenocortical adenoma, who presented with precocious puberty and Cushing’s syndrome. After work-up, the patient underwent laparoscopic adrenalectomy. The excised adrenal mass weighed 21 g and measured 3.5 cm in maximum dimension. Histological examination demonstrated no features suggestive of aggressive biological behaviour. The patient had no features of recurrent or metastatic disease and had prepubertal testosterone levels with suppressed hypothalamic-pituitary-adrenal axis twelve months after the surgery. A discussion of this case and a review of the literature on functional OATs in the pediatric population are presented.